Farklı kuvvet sistemine sahip iki yüz maskesinin maksilla üzerindeki etkilerinin karşılaştırılması - Çetinkaya Tokmak, Ebru (My University, 2000)
Protraksiyon headgearleri, maksiller retrognati olgularında sıklıkla kullanılmaktadır. Ancak, protraksiyon sırasında maksillada oluşturdukları saat yönünün tersine rotasyon, klasik protraksiyon headgearlerinin open bite eğilimi olan maksiller retrognati olguların tedavisinde kullanılmasını engellemektedir. Bu etkiyi ortadan kaldırmak amacıyla, klasik kuvvet uygulama noktasının yerine, kuvvet uygulama noktası maksillanın iskeletsel rezistans merkezinin hizasına taşınmıştır. Bu çalışmada, biri klasik protraksiyon headgeari ile diğeri ise kuvvet uygulama noktası maksillanın iskeletsel rezistans merkezinin hizasına taşınmış 2 grup karşılaştırılmıştır. Birinci grup, 5 kız, 4 erkek, 9 olgudan, ikinci grup ise, 6 kız, 5 erkek, 11 olgudan oluşmuştur. Her iki grupta olguların yaşları 7 ile 10 arasındadır. Tedavi protraksiyon işleminden hemen önce uygulanan, 1 haftalık RPE işlemi ile başlamıştır. Bundan sonra, protraksiyon işlemi başlamış ve tek taraflı 450 gr kuvvet uygulanmıştır. Tedaviye başlamadan hemen önce ve tedavinin 3. ve 6. aylarında lateral sefalometrik filmler alınmış ve araştırma bu filmler üzerinde yürütülmüştür. 8 açısal, 11 lineer ölçüm istatistiksel olarak Wilcoxon Testi ile istatistiksel olarak incelenmiş ve gruplar arası farkın önemi Mann Whitney U Testi ile değerlendirilmiştir. 3. ayın sonunda her iki grupta da maksilla ileri hareket etmiştir. 1. grupta SNA açısı 2.440, Nper-PA uzunluğu 2.44mm, TV-ANS uzunluğu 2.44mm, TV-A uzunluğu 2.89 mm, TV-MM uzunluğu 3.11mm, artmış, 2. grupta SNA açısı 2.360, Nper-PA uzunluğu 2.77mm, TV-ANS uzunluğu 2.82mm, TV-A uzunluğu 1.82 mm, TV-MM uzunluğu 2.59mm, artmıştır. 1. grupta maksilla, saat yönünün tersine rotasyon yapmıştır. SN-PP açısı -10 azalırken, TH-PNS uzunluğu 1.56 mm artmıştır. 2. grupta ise maksilla saat yönünde rotasyon yapmıştır. PP-OP açısı 7.450, TH-ANS uzunluğu 1.73 mm, SN-OP açısı 6.180 artmıştır. 2. grupta maksiller kesici dişlerde palatinal tipping oluşmuştur. U1-SN açısı -5.820, U1-PPA açısı -6.550 azalmıştır. 6. ayın sonunda, her iki grupta da maksilla ileri hareket etmiştir. 1. grupta SNA açısı 3.110, Nper-PA uzunluğu 5.11mm, TV-ANS uzunluğu 1.44mm, TV-A uzunluğu 3 mm, TV-MM uzunluğu 4.89 mm artmış, 2. grupta SNA açısı 3.890 Nper-PA uzunluğu 5.36 mm, TV-ANS uzunluğu 1.91mm, TV-A uzunluğu 2.45 mm, TV-MM uzunluğu 3.59mm, artmıştır. 1. grupta maksilla, saat yönünün tersine rotasyon yapmıştır. SN-PP açısı -2.440azalırken, TH-PNS uzunluğu 2.44 mm artmıştır. 2. grupta ise maksilla saat yönünde rotasyon yapmıştır. PP-OP açısı 11.090, TH-ANS uzunluğu 1.45 mm, SN-OP açısı 8.910 artmıştır. 2. grupta maksiller kesici dişlerde palatinal tipping oluşmuştur. U1-SN açısı -80, U1-PPA açısı -8.550 azalmıştır. Kuvvet uygulama noktasının maksillanın iskeletsel rezistans merkezinin hizasına taşınmasıyla maksillada saat yönünde rotasyon elde edilmiştir. Sonuç olarak bu tip kuvvet sisteminin maksiller retrognati vakalarında etkili bir şekilde kullanılabileceği düşünülmektedir. COMPARISON OF TWO DIFFERENT FORCE SYSTEMS ON MAXILLARY ORTHOPEDİC PROTRACTION SUMMMARY Protraction headgears are frequently used in maxillary retrognathic cases. However, the counterclockwise rotation produced during protraction prevents the usage of protraction headgears in maxillary retrognathic cases with open-bite tendency. In order to eliminate this effect the point of force application was carried to the level of skeletal center of resistance of the maxilla, instead of the conventional point of force application. In this study, we compared two patient groups, one treated with the conventional protraction headgear, and the other one treated with protraction headgear in which the point of force application was carried to the level of skeletal center of resistance of the maxilla. Group one was comprised of 9 cases, 5 of which were girls and 4 boys. As for group two, it was comprised of 11 patients, 6 girls and 5 boys. The age in both groups ranged between 7 to 10 years. Treatment began in both groups with one week of RPE prior to the protraction headgear application. After that the protraction procedure was begun and in both groups a force of 450 gms was applied unilaterally. Lateral cephalograms were taken, prior to treatment, 3 and 6 months into treatment as well, and study was carried out on these films. 8 angular and 11 linear measurements were statistically investigated by means of Wilcoxon test and the significance of the difference between the two groups was evaluated using the Mann Wittney U test. At the end of the third month, maxillae moved forward in both groups. In the first group, SNA angle, Nper-PA length, TV-ANS length, TV-A length, TV-MM length increased, 2.440, 2.44mm, 2.44mm, 2.89 mm, 3.11mm, respectively, in the second group, SNA angle, Nper-PA length, TV-ANS length, TV-A length, TV-MM length increased, 2.360, 2.77mm, 2.82mm, 1.82 mm, 2.59mm, respectively. In the first group, maxillae made counterclockwise rotation. While SN-PP angle decreased -10, TH-PNS length increased 1.56 mm. In the second group, maxillae made clockwise rotation. PP-OP angle , TH-ANS length, SN-OP angle increased, 7.450, 1.73 mm, 6.180, respectively. In the second group, palata tipping occured in maxillary incisors. U1-SN angle and U1-PPA açısı decreased , -5.820, -6.550, respectively. At the end of the sixth month maxillae moved forward in both groups. In the first group, SNA angle, Nper-PA length, TV-ANS length, TV-A length, TV-MM length increased, 3.110, 5.11mm, 1.44mm, 3mm, 4.89mm, respectively, in the second group, SNA angle, Nper-PA length, TV-ANS length, TV-A length TV-MM length decreased, 3.890, 5.36mm, 1.91mm, 2.45 mm, 3.59mm, respectively. In the first group, maxillae made counterclockwise rotation. While SN-PP angle decreased -2.440, TH-PNS length increased 2.44 mm. In the second group, maxillae made clockwise rotation. PP-OP angle, TH-ANS length, SN-OP angle increased, 11.090, 1.45 mm, 8.910, respectively. In the second group, palatal tipping occurred in maxillary incisors. U1-SN angle, U1-PPA angle decreased, -80, -8. 550, respectively. By carrying the point of force application to the skeletal center of resistance of maxilla, clockwise rotation is obtained. As a result, this type of force system can be used effectively in maxillary retrognatic cases with open bite tendency.
Keywords: DİŞHEKİMLİĞİ; ORTODONTİ